Polymers for tissue engineering - Shoichet, M. S. (Molly S.); Hubbell, J. A. (Jeffrey A.) (Journal of biomaterials science. Polymer edition ;, 1998)
The articles included in this text highlight the important advances in polymer science that impact tissue engineering. The breadth of polymer science is well represented with the relevance of both polymer chemistry and morphology emphasized in terms of cell and tissue response.